Palaeobiodiversity and palaeoenvironments of African Cretaceous and Miocene amber deposits - (:unkn) unknown (My University, 2021)
Amber deposits are numerous and distributed worldwide. However, most of the deposits known today are found in the Northern Hemisphere (mostly former Laurasia), while reports of fossiliferous amber are scarce in the Southern Hemisphere or former Gondwana. This disparity seems due to a lack of access and prospection in many Gondwanan regions. The discovery of two new Gondwanan deposits, one from the Cretaceous of Congo, the other from the Miocene of Ethiopia, provides unique African, Gondwanan, or fossil occurrences of diverse arthropods as well as plants. Congo amber, produced by a gymnosperm, likely of the Cheirolepidiaceae family, illustrates a gymnosperm-dominated forest environment. Among the resin inclusions, Diptera and Hymenoptera are dominant. They reveal a locally humid environment, under hot, semiarid, global climate, that developed at the dawn of Gondwanan breakup. Miocene Ethiopian amber illustrates a swamp or marsh environment in a tropical rain forest. The cryptogam and arthropod inclusions revealed in amber indicate similarities with contemporaneous ambers from Dominican Republic and Mexico. These affinities suggest a common Gondwanan origin of the floristic and faunistic components, providing information on Cenozoic biogeographical evolution of taxa.
Keywords: African Research